HUBUNGAN SKOR GLASGOW COMA SCALE (GCS) DENGAN JUMLAH TROMBOSIT PADA PASIEN CEDERA KEPALA DI IGD RSUD ULIN BANJARMASIN - Yutami, Annisa; Sikumbang, Kenanga Marwan; Asnawati, Asnawati (Berkala Kedokteran, 2016)
Abstract: Head injuries are a public health and a serious socio-economic problems in the world. Head injury classified quantitatively using the Glasgow Coma Scale (GCS) score. Consumptive coagulopathy that often arises in patients with head injury associated with a tenfold adjusted risk of death. Consumptive coagulopathy marked by a decrease in the number of platelets. The purpose of the study was to analyze the relationship between GCS score with total platelet count in head injury patients at Emergency Department Ulin General Hospital Banjarmasin. This study was an observational analytic cross sectional study. Seventy three samples were obtained according to the inclusions criteria with 28 mild head injury patients, 26 moderate head injury patients, and 19 severe head injury patients. Seven patients had thrombocytopenia, from moderate head injury and severe head injury groups. From statistical test using one way ANOVA with confidence level of 95% was obtained p=0.402. It can be concluded that there is no relationship between GCS score with total platelet count in head injury patients at Emergency Department Ulin General Hospital. Keywords: head injury, GCS, platelet count Abstrak: Cedera kepala merupakan masalah kesehatan masyarakat dan sosial ekonomi yang serius di dunia. Cedera kepala diklasifikasikan secara kuantitatif menggunakan skor Glasgow Coma Scale (GCS). Koagulopati konsumtif yang sering muncul pada pasien cedera kepala dapat meningkatkan risiko kematian menjadi sepuluh kali lipat. Koagulopati konsumtif ditandai dengan penurunan jumlah trombosit. Tujuan penelitian untuk mengetahui apakah terdapat hubungan antara skor GCS dengan jumlah trombosit pada pasien cedera kepala di IGD RSUD Ulin Banjarmasin. Penelitian ini bersifat observasional analitik cross sectional. Didapatkan 73 sampel yang sesuai dengan kriteria inklusi, dengan perincian 28 pasien cedera kepala ringan (CKR), 26 pasien cedera kepala sedang (CKS), dan 19 pasien cedera kepala berat (CKB). Tujuh pasien mengalami trombositopenia, dari kelompok pasien cedera kepala sedang dan cedera kepala berat. Dari uji statistik  menggunakanone-way ANOVA dengan tingkat kepercayaan 95% didapatkan nilai p=0,402. Dapat disimpulkan bahwa tidak terdapat hubungan antara skor GCS dengan jumlah trombosit pada pasien cedera kepala di IGD RSUD Ulin Banjarmasin. Kata-kata Kunci: cedera kepala, GCS, jumlah trombosit